The five dysfunctions of a team participant workbook - Lencioni, Patrick 1965- (Pfeiffer ;, 2007)
Annotation
Includes bibliographical references
Keywords: Teams in the workplace; Social groups; Leadership; Personnel management; Psychology, Industrial; Group Processes; Personnel Management; Workplace -- organization & administration; Workplace -- psychology; Institutional Management Teams; Équipes de travail; Dynamique des groupes; Personnel; Direction; Psychologie du travail; Teamwork; Problems and exercises